SHIFTING WEED COMPOSITIONS AND BIOMASS PRODUCTION IN SWEET CORN FIELD TREATED WITH ORGANIC COMPOSTS AND CHEMICAL WEED CONTROLS - Marulak Simarmata; Chrisman Dani Sitanggang; Djamilah Djamilah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
The objectives of the research were to study the shift of weed compositions in sweet corn field treated with organic compost and chemical weed controls and to compare the effect of treatment combinations on weed growth, weed biomass and sweet corn biomass. The research was conducted in Bengkulu, Indonesia, from April to July 2014. Results showed that the number of weed species decreased after the trials from 14 to 13. There was a shift in weed compositions because 5 species of weeds did not emerge after the trials, but 4 new species were found. Chemical weed control using a herbiside mixture of atrazine and mesotrione applied during postemergence was the most effective method to control weeds, which was observed on decreased weed emergence and weed biomas down to 22.33 and 25.00 percent of control, respectively. Subsequently, biomass production of sweet corn increased up to 195.64 percent with the same trials. Biomass of weeds and sweet corn were also affected by the organic composts. Weed biomass was inhibited with treatment of composted empty fruith bunches of oilpalm, whereas significantly increased of sweet corn biomass were observed in the plots of organic manure.